2013
DOI: 10.1128/aem.02628-12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Salmonella enterica Serovar Enteritidis Infection on the Development of the Cecum Microbiota in Newly Hatched Chicks

Abstract: Terminal restriction fragment length polymorphism and quantitative PCR showed that the cecal microbiota of chicks up to the age of 21 days was dominated by representatives of the orders Enterobacteriales, Clostridiales, and Lactobacillales. Salmonella enterica serovar Enteritidis infection caused the greatest changes in the gut microbiota when 1-day-old chicks were infected, compared with the infection of 4-and 16-day-old chicks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 14 publications
13
44
0
Order By: Relevance
“…These results indicate that S. typhimurium infection influenced the composition of the cecal microbiota in chickens. The changes in the composition of gut microbiota were also observed in animals infected with non-typhoid serovars of Salmonella (Barman et al, 2008;Juricova et al, 2013;Videnska et al, 2013), which were associated with inflammation (Stecher et al, 2007;Barman et al, 2008). Thus, these changes in the microbiotal composition induced by S. typhimurium infection, as observed in our study, may contribute to the processes of mucosal injury (Tamboli et al, 2004;Sokol et al, 2006), and support the observed results of a reduction in the villus-height/crypt-depth ratio of the ileum and an elevated apoptotic index of ileal epithelial cells in challenged broilers.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These results indicate that S. typhimurium infection influenced the composition of the cecal microbiota in chickens. The changes in the composition of gut microbiota were also observed in animals infected with non-typhoid serovars of Salmonella (Barman et al, 2008;Juricova et al, 2013;Videnska et al, 2013), which were associated with inflammation (Stecher et al, 2007;Barman et al, 2008). Thus, these changes in the microbiotal composition induced by S. typhimurium infection, as observed in our study, may contribute to the processes of mucosal injury (Tamboli et al, 2004;Sokol et al, 2006), and support the observed results of a reduction in the villus-height/crypt-depth ratio of the ileum and an elevated apoptotic index of ileal epithelial cells in challenged broilers.…”
Section: Discussionmentioning
confidence: 81%
“…At the initiation of intestinal infection of broiler chickens, S. typhimurium must outcompete the resident microbiota of the distal ileum and cecum and penetrate the mucosal epithelium (Berndt et al, 2007). After overcoming colonization resistance, S. typhimurium disrupts the intestinal ecosystem in mammals and chickens, leading to infection of the gastrointestinal tract (Stecher et al, 2007;Barman et al, 2008;Juricova et al, 2013;Videnska et al, 2013). Furthermore, Salmonella infections can cause infected epithelial cell shedding from the villus surface, resulting in villus blunting and loss of absorptive surfaces (Wallis and Galyov, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…After PCR, the Ct values of the genes of interest were subtracted from an average Ct value of amplifications performed with universal primer pairs for the domain Bacteria (ΔCt). The relative amount of each taxon in the total bacterial population was finally calculated as 2 -ΔCt [15,16]. …”
Section: Methodsmentioning
confidence: 99%
“…We were therefore interested whether the inflammation induced by Salmonella infection will or will not affect the development and composition of gut microbiota in chickens. Our previous results using T-RFLP and quantitative real time PCR indicated that the changes in gut microbiota in chickens are not as dramatic as one would expect from data in other models of host - pathogen interactions [12-14,16]. In this study we have therefore used pyrosequencing of V3 and V4 variable regions of 16S rRNA genes to characterize the consequences of S .…”
Section: Introductionmentioning
confidence: 96%